2014
DOI: 10.1152/ajpregu.00191.2014
|View full text |Cite
|
Sign up to set email alerts
|

Two-week normobaric intermittent hypoxia exposures enhance oxyhemoglobin equilibrium and cardiac responses during hypoxemia

Abstract: Intermittent hypoxia (IH) is extensively applied to challenge cardiovascular and respiratory function, and to induce physiological acclimatization. The purpose of this study was to test the hypothesis that oxyhemoglobin equilibrium and tachycardiac responses during hypoxemia were enhanced after 14-day IH exposures. Normobaric-poikilocapnic hypoxia was induced with inhalation of 10% O2 for 5-6 min interspersed with 4 min recovery on eight nonsmokers. Heart rate (HR), arterial O2 saturation (SaO 2), and end-tida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 56 publications
5
29
0
Order By: Relevance
“…Significant reductions in PetCO 2 during SH and IH sessions indicate however that subjects hyperventilated during both types of hypoxic exposure (Figure 2). The hypoxic hyperventilatory response was nevertheless relatively modest since V E increased by <2 L·min −1 and PetCO 2 decreased by <3 mmHg on average whatever the hypoxic condition, which is consistent with previous observations during SH and IH conditioning sessions [~50-min IH with 5–6 min FiO 2 = 0.10–4 min FiO 2 = 0.21 (Zhang et al, 2014); 1-h SH or IH at SpO 2 = 80–90% (Rodway et al, 2007)]. This modest increase in ventilation probably contributed to the absence of significant discomfort reported by all subjects during both SH and IH sessions.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Significant reductions in PetCO 2 during SH and IH sessions indicate however that subjects hyperventilated during both types of hypoxic exposure (Figure 2). The hypoxic hyperventilatory response was nevertheless relatively modest since V E increased by <2 L·min −1 and PetCO 2 decreased by <3 mmHg on average whatever the hypoxic condition, which is consistent with previous observations during SH and IH conditioning sessions [~50-min IH with 5–6 min FiO 2 = 0.10–4 min FiO 2 = 0.21 (Zhang et al, 2014); 1-h SH or IH at SpO 2 = 80–90% (Rodway et al, 2007)]. This modest increase in ventilation probably contributed to the absence of significant discomfort reported by all subjects during both SH and IH sessions.…”
Section: Discussionsupporting
confidence: 91%
“…Changes in arterial blood pressure during acute hypoxic exposure result from the opposite effect of hypoxia-induced peripheral vasodilation (Crawford et al, 2006) and sympathetic activation (Halliwill et al, 2003). Previous studies reported inconsistent changes in arterial blood pressure during acute SH or IH exposure with no change [~50-min IH with 5–6 min FiO 2 = 0.10–4 min FiO 2 = 0.21 (Zhang et al, 2014)] or slight increase [1-h SH at SpO 2 = 80% (Lusina et al, 2006), 1-h SH or IH at SpO 2 = 80–90% (Rodway et al, 2007), 1-h IH with 5–7 min normocapnic rebreathing–5–7 min FiO 2 = 0.21 (Bernardi et al, 2001b)]. In the present study both SH and IH induced a significant increase in blood pressure (Figure 3) which may be of larger magnitude compared to some previous studies due to the relatively low target SpO 2 (70–80%).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The IHT mediated decline in left ventricular TH content and downward trend in TH positive fibers supports an evolving shift in myocardial autonomic balance in favor of a protective parasympathetic influence. This conclusion is further supported by observations in humans where an enhanced vagal control over the heart, accompanied by decrease tachycardic responses to hypoxia stimulus, following 14 d of intermittent hypoxia exposure was demonstrated [Zhang et al, 2014]. …”
Section: Discussionsupporting
confidence: 75%